A política trabalhista como proposta conciliadora dos conflitos entre trabalho e capital: (1930-1945) - Santos, Adenilson Mendes dos (2009)
This dissertation is part of the History of Political Relations, bringing as overall theme the labor policy for the period 1930 to 1945. It shows the importance of the state as mediator of conflicts between labor and capital and analyzes the labor policy of Getúlio Vargas as an alternative for solving these conflicts. Uses some words of President Vargas, the reports submitted for consideration in Congress from 1933 to 1937, the reports sent to the President by the Ministers of Labor and the law of the time. Thus, the case in speeches of the president, his intentions in regard to social workers in Brazil, to present new proposals for the performance of the state as mediator of conflicts between employers and employees. At the same time, makes an analysis of the social labor issue in the First Republic, seeking there the foundations of the formation of the social labor law that has been refined at Vargas. From this analysis, compares the state's interest in these issues, establishing differences between the governments of the First Republic and the period studied. From the legislation studied, there is a policy developed from the creation of the Ministry of Labor, Industry and Trade, an institution created to resolve issues relating to urban work in order to meet the three classes defined in the name of the ministry . Works with the hypothesis that, within the relations of production, the importance of the public power, represented by the state is so great that without it, conflicts tend to be pronounced.